A review of Scaphochlamys (Zingiberaceae) from borneo, with description of eleven new species - Ooi, Im Hin; Meekiong, K.; Wong, Sin Yeng (Magnolia Press, 2017)
In the present paper, the genus Scaphochlamys from Borneo is revised. Twenty-four species are recognised, of which 11 are new species: S. durga, S. graveolens, S. hasta, S. lanjakensis, S. lucens, S. nigra, S. multifolia, S. penyamar, S. pseudoreticosa, S. scintillans, and S. uniflora. Scaphochlamys depressa is treated as a synonym to S. argentea. The Bornean species are arranged into six informal groups based on morphological characteristics: Anomala Group, Calcicola Group, Graveolens Group, Limiana Group, Petiolata Group, and Polyphylla Group. The paper includes an overview of morphological characteristics, identification keys to groups and species, and species descriptions. A discussion of the recently recognized generic segregate, Borneocola is included. © 2017 Magnolia Press.